PENDIDIKAN ISLAM DI BRUNEI DARUSSALAM - Wasiah Wasiah; Fitri Fitri (CV. ADIBA AISHA AMIRA, 2022)
Brunei or Brunei Darussalam, a country that is relatively small compared to Malaysia and Indonesia, but Brunei is an Islamic kingdom that plays an important role in maintaining Islamic values ​​in the midst of its people. Brunei or also called the Malay Islamic Kingdom (MIB) really makes Islam its national ideology. Islam is the majority religion in Brunei today, almost 100% of Brunei's indigenous people embrace Islam 95% of Brunei's non-Muslim population are immigrants from the Philippines, India, China , Etc. In total, 98% of Brunei's natives are Muslim and 40% of immigrants are Muslims. When combined, 78% of Brunei's population is Muslim. The progress and development of Islam became more evident during the reign of Sultan Bolkiah (5th sultan) whose territory covered Suluk, Selandung, the entire island of Borneo, the Sulu Archipelago, the Balabac Islands, Banggi Island, Balambangan Island, Matanani, and north of Palawan Island to Manila. The progress and development of Islam became more evident during the reign of Sultan Bolkiah (5th sultan) whose territory covered Suluk, Selandung, the entire island of Borneo, the Sulu Archipelago, the Balabac Islands, Banggi Island, Balambangan Island, Matanani, and north of Palawan Island to Manila.